Decision-Making Process for the Management of Acute Stroke in Patients on Oral Anticoagulant: From Guidelines to Clinical Routine - Sibon, Igor; Mazighi, Mikael; Smadja, Didier (Frontiers in Neurology, 2022)
Background: The occurrence of both ischaemic (IS) and haemorrhagic stroke in patients on anticoagulation is a major issue due to the frequency of their prescriptions in westernised countries and the expected impact of anticoagulant activity on recanalization during an IS or on the outcomes associated with intracerebral haemorrhage (ICH). Several guidelines are available but sometimes differ in their conclusions or regarding specific issues, and their application in routine emergency settings may be limited by particular individual issues or heterogeneous local specificities. Methods: Based on the current guidelines and additional published data, the algorithms proposed in this paper aim to help the decision-making process regarding stroke management in the setting of concurrent anticoagulants by addressing specific clinical situations based on clinical variables commonly encountered in real-world practise. Results: For patients on non–vitamin K oral anticoagulants, reversion can be achieved with specific antidotes, but only idarucizumab, the specific dabigatran antidote, is indicated in both IS and ICH. Due to the low risk of a prothrombotic effect, idarucizumab can be immediately used in IS patients eligible for thrombolysis before the dabigatran concentration is known. To optimise ICH management, the time since symptom onset, with thresholds proposed at 6 and 9 hours based on the expected timing of haematoma expansion, could also to be taken into account. Conclusions: Anticoagulant reversal in patients presenting with a stroke remains a major issue, and algorithms based on a step-by-step approach may be useful for clinical practise. Real-life studies strongly support the benefits of idarucizumab availability in stroke units and emergency departments.